Evaluation of Syzygium myrtifolium leaves extract as an eco-friendly inhibitor for steel in reinforced concrete - Alwi Syahara, Muhammad (ALKIMIA, 2023)
Reinforced concrete is a concrete mixture that is reinforced with steel to strengthen the concrete in a building construction. One of the problems with steel is corrosion which can damage the concrete structure. One way to inhibit the corrosion process is to inhibit the corrosion rate using organic/eco-friendly inhibitors. A potential eco-friendly inhibitor is Syzygium myrtifolium leaves. This study aims to determine the corrosion rate and inhibition efficiency in reinforcing steel (BjTP) 280. This research method begins with maceration of Syzygium myrtifolium leaves using 96% alcohol for 96 hours. Then BjTP 280 is immersed in concentrated extract with variations in immersing time of 0 hours, 24 hours, 72 hours, 120 hours, and 168 hours. Furthermore, BjTP 280 is used in K350 quality concrete structures. Calculation of corrosion rate using weight loss method based on ASTM G 31-72, corrosion testing based on ASTM C 876-91 by immersing concrete in 3.5% NaCl corrosive media solution and flowing 6 V DC current for 14 days. The corrosion rate (mm/year) in each variation of immersion in inhibitor decreased, respectively 875.95 (0 hours); 298.66 (24 hours); 99.55 (72 hours); 79.73 (120 hours); 42.66 (168 hours). Meanwhile, the inhibition efficiency value (%) increased successively, namely -% (0 hours); 65,9% (24 hours); 88,63% (72 hours); 90,93% (120 hours); 95,12% (168 hours). The results showed the best corrosion rate reduction of 42.66 mm/year with inhibition efficiency of 95,12% obtained at 168 hours of immersion.